Internet and fuzzy based control system for rotary kiln in cement manufacturing plant, ISSN / e-ISSN 1875-6883 / 1875-6891 - Zermane Hanane; Mouss Leila Hayet (International Journal of Computational Intelligence Systems, 2017)
This paper develops an Internet-based fuzzy control system for an industrial process plant to ensure the remote and fuzzy control in cement factories in Algeria. The remote process consists of control, diagnosing alarms occurs, maintaining and synchronizing different regulation loops. Fuzzy control of the kiln ensures that the system be operational at all times, with minimal downtime. Internet technology ensures remote control. The system reduces downtimes and can guided by operators in the main control room or via Internet.